Transformasi Nilai Pendidikan Agama Islam melalui Ekstrakurikuler Hadrah pada Siswa SDN 1 Kepanjenkidul Kota Blitar - Rohman, Miftakhul; Sahid, Nur (SINDA: Comprehensive Journal of Islamic Social Studies, 2025)
Islamic Religious Education plays a strategic role in shaping students’ religious character from an early age. However, Islamic Religious Education learning in elementary schools is often still focused on cognitive aspects, so the internalization of values has not been optimal. This study aims to examine the process of transforming Islamic Religious Education values through hadrah extracurricular activities at SDN Kepanjenkidul, Blitar City. This research employs a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The results show that hadrah extracurricular activities effectively transform Islamic Religious Education values, such as religiosity, discipline, responsibility, togetherness, and tolerance. These values are instilled through the habituation of chanting shalawat, group cooperation, and the exemplary role of the instructor. Hadrah functions not only as an Islamic musical art activity but also as a contextual medium for value education that touches students’ emotional aspects. Therefore, hadrah extracurricular activities can be considered an integral part of supporting Islamic Religious Education learning in elementary schools.